2015
DOI: 10.1245/s10434-014-4351-9
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Mutations and Genetic Heterogeneity at the CDKN1B Locus in Small Intestinal Neuroendocrine Tumors

Abstract: This study corroborates the finding of CDKN1B as a potential haplo-insufficient tumor suppressor gene characterized by inter- and intratumor heterogeneity in SI-NETs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 28 publications
2
56
2
1
Order By: Relevance
“…Cell cycle deregulation may thus be one potential mechanism in SI-NET tumorigenesis. A further study aimed to re-sequence a clinically well-characterized cohort consisting of 362 SI-NET samples from 200 patients for CDKN1B mutations and to investigate possible genotypephenotype correlations (Crona et al 2015). This study confirmed CDKN1B as a potential tumour suppressor gene in SI-NET.…”
Section: Small Intestinal Netmentioning
confidence: 72%
“…Cell cycle deregulation may thus be one potential mechanism in SI-NET tumorigenesis. A further study aimed to re-sequence a clinically well-characterized cohort consisting of 362 SI-NET samples from 200 patients for CDKN1B mutations and to investigate possible genotypephenotype correlations (Crona et al 2015). This study confirmed CDKN1B as a potential tumour suppressor gene in SI-NET.…”
Section: Small Intestinal Netmentioning
confidence: 72%
“…The genomic landscape of SI-NETs has been investigated with exome coverage in close to 100 tumor samples (136,137). Recurrent mutations were only identified in the CDKN1B gene with a mutation prevalence of 9% of SI-NET patients (136,137,138). Instead, the most frequent genomic alteration is hemizygous deletions affecting chromosome 18q (133,136,137,139).…”
Section: Small Intestinal Netsmentioning
confidence: 99%
“…Whether these are the consequences of independent tumor formation or metastatic spread remain to be settled (144,145). Recent studies highlighted that a subset of SI-NETs show pronounced genetic heterogeneity within and between tumor lesions (136,138). Korpershoek et al (150) determined, by using LOH markers, that there is genetic heterogeneity within different areas of selected PCCs and PGLs.…”
Section: Genetic Heterogeneity and Tumor Evolutionmentioning
confidence: 99%
“…Mutations occurring in CDKN1B are loss-of-function truncating mutations that occur throughout the gene. Mutational status does not appear to correlate with expression of p27 (the protein product of CDKN1B) and has no detectable association with clinical characteristics or survival (4). Given the low frequency of mutations in this putative tumor suppressor gene, and the absence of other obvious pathogenetic genome alterations, we hypothesized that alternative mechanisms such as epigenetic dysregulation are likely to play a role in these tumors (5).…”
Section: Introductionmentioning
confidence: 99%
“…The most frequent genomic event identified in SINETs is loss of heterozygosity (LOH) at chromosome 18, occurring in 60% to 78% of tumors (2,3); more recently, recurrent mutations in the cell cycle regulator CDKN1B (cyclin-dependent kinase inhibitor 1B) have been identified in approximately 8% of tumors in large-scale sequencing studies (3,4). Mutations occurring in CDKN1B are loss-of-function truncating mutations that occur throughout the gene.…”
Section: Introductionmentioning
confidence: 99%